2019
DOI: 10.20435/inter.v20i3.1759
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in nutrition therapy within the intensive care setting of a Brazilian teaching hospital

Abstract: The quality of nutritional therapy was evaluated in an adult intensive care unit in a Brazilian teaching hospital, using ten indicators expressing target quality rates were selected from a list compiled by the Clinical Nutrition Task force of the Brazilian chapter of the International Life Sciences Institute (ILSI-Brasil). It was observed that the use of quality indicators of nutritional therapy allowed the identification of compliance and nonconformity processes, which still need additional adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Detecting nutritional risk by performing nutritional screening allows the nutrition support team to take early initiative, even in patients with apparently adequate total body weight, whereas SGA is primarily effective in recognizing current malnutrition [ 7 , 26 , 27 , 28 , 29 ]. Many studies have demonstrated a deficiency in screening nutrition within 24 h of admission, assessment, and even nutritional reassessment [ 8 , 9 , 10 , 13 ]. In studies involving clinical and surgical patients, the nutritional assessment corresponded to 30.7% and 75%, respectively [ 11 , 12 ], which agrees with the current study, the nutritional assessment being achieved in 55.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detecting nutritional risk by performing nutritional screening allows the nutrition support team to take early initiative, even in patients with apparently adequate total body weight, whereas SGA is primarily effective in recognizing current malnutrition [ 7 , 26 , 27 , 28 , 29 ]. Many studies have demonstrated a deficiency in screening nutrition within 24 h of admission, assessment, and even nutritional reassessment [ 8 , 9 , 10 , 13 ]. In studies involving clinical and surgical patients, the nutritional assessment corresponded to 30.7% and 75%, respectively [ 11 , 12 ], which agrees with the current study, the nutritional assessment being achieved in 55.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of hospitalized patients have some degree of malnutrition and require nutritional therapy [ 2 ]. Although there is a high prevalence of malnutrition, there are few studies considering quality indicators in nutritional therapy (QINT) [ 8 , 9 , 10 , 11 , 12 , 13 ]. This is important, as these indicators minimize energy and protein imbalance and weight loss, and also help prevent adverse outcomes and clinical complications, including increased infection rate, impaired wound healing, a longer length of hospital stay, higher treatment costs, and mortality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation